Kajian Hukum Administrasi Negara Terhadap Pelaksanaan Pemilihan Kepala Daerah Di Indonesia (Studi Pada Pemilihan Kepala Daerah Kabupaten Serdang Bedagai Tahun 2020) - Ahmad Alhadi (Universitas Islam Sumatera Utara, 2022)
The emergence of the idea of direct Pilkada is basically a follow-up process from a strong desire to improve the quality of democracy in the regions that is being started. Direct local elections are expected to produce credible leaders who are supported by the community. The formulation of the problem in this thesis is how the legal arrangements for implementing regional head elections in Indonesia according to State Administrative Law, how the implementation of regional head elections in Serdang Bedagai Regency is studied from State Administrative Law, how are the obstacles to implementing regional head elections in Serdang Bedagai Regency in terms of State Administrative Law and solution to overcome it. The results of the study indicate that the legal regulation of the implementation of regional head elections in Indonesia according to the State Administrative Law is regulated in Perpu No. 2 of 2020 concerning the simultaneous election of blood heads (Pilkada). The obstacle to the implementation of the Serdang Bedagai Regional Head Election (Pilkada) Simultaneously in carrying out the simultaneous Pilkada during the Covid-19 pandemic is the existence of money politics disguised in social assistance. To uphold integrity in the implementation of the Pilkada, there must be a commitment for both the Pilkada participants and the implementers of community discipline to take part in the 2020 simultaneous Pilkada so that the obstacles and challenges of the Pilkada can be minimized. Keywords: Implementation of Election, Regional Head.